Sistem Pendukung Keputusan dalam Skema Pengusulan Awal Jabatan Fungsional Dosen Menggunakan Sistem Inferensi Fuzzy Tipe Mamdani - Tomi Tamara; Efri Yandani (INTECOMS: Journal of Information Technology and Computer Science, 2019)
This study aims to build a WEB-based decision support system to simplify the process of assessing credit numbers for initial proposals for functional lecturers. With this system the lecturer will be made easier in terms of completing the required files and can quickly and accurately calculate the amount of cum that is obtained. The resulting system uses the Mamdani type Fuzzy Inference System (FIS) to analyze the variables used in assessing lecturers' functional position credit numbers. Furthermore, the system development stage uses the waterfall model. System design analysis includes outputs, inputs, file structures, programs, workflows, hardware and software needed. Then this system will certainly greatly reduce the use of paper because it is based on electronics. So later, with this system, it is expected that the credit score submission process does not take a long time and can increase the number of lecturers who have functional positions in STIKES Dharma Landbouw. Keywords: Fuzzy Logic, FIS, Decision Support System, Mamdan